The Development of Teacher’s Professional Competence: A Theoretical Review - Rahmah, Syarifah; Kadi, Titi (Institut Agama Islam Negeri Lhokseumawe, 2022)
The functionalization of teachers as the primary contributor to educational quality is demonstrated by their mastery of professional facets. The purpose of this study is to design and examine a model for teacher professional development. a qualitative study design using literary methods. Using the keywords